Endocan, a novel glycoprotein with multiple biological activities, may play important roles in neurological diseases - Liu, Shuo; Bai, Tao; Feng, Juan (Frontiers in Aging Neuroscience, 2024)
Endothelial cell specific-1 (ESM-1), also known as endocan, is a soluble dermatan sulfate proteoglycan that is mainly secreted by endothelial cells. Endocan is associated with tumorigenesis and cancer progression and is also related to cardiovascular disorders, autoimmune diseases, and sepsis. The phenylalanine-rich region and linear polysaccharide of endocan are necessary for the protein to exert its biological functions. Elevated plasma endocan levels reflect endothelial activation and dysfunction. In addition, endocan participates in complex inflammatory responses and proliferative processes. Here, we reviewed current research on endocan, elaborated the protein's structure and biological functions, and speculated on its possible clinical value in nervous system diseases. We conclude that endocan may be a glycoprotein that plays an important role in neurological disorders.